The Criminal Law Enforcement Policy in Online Prostitution Treatment - Harjanto Mukti Eko Utomo; Umar Ma'ruf (Universitas Islam Sultan Agung, 2020)
The purpose of this research to find out and analyze criminal law enforcement policies in efforts to tackle online prostitution at the Central Java Regional Police Ditkrimsus, obstacles in criminal law enforcement policies in efforts to tackle online prostitution at the Ditkrimsus of Central Java Police and criminal law enforcement policies that should be implemented to tackle online prostitution in the Indonesian Police. The approach method used is juridical normative and juridical socio-logical method, the specifications in the research are descriptive analytical, population and sampling methods are all objects or all symptoms or all events or all units to be studied, data collection techniques use literature study and interviews, data analysis used is qualitative. Problems are analyzed using Progressive Law Theory, Law Enforcement Theory and Effectiveness Theory. Criminal law enforcement policies in efforts to tackle online prostitution at the Central Java Regional Police Ditkrimsus are in accordance with existing regulations. Obstacles in criminal law enforcement policies in efforts to tackle online prostitution at the Central Java Regional Police Ditkrimsus and solutions to overcome these obstacles. According to the author, do research by interviewing members of the Central Java Police that Barriers to law enforcement against online prostitution in the Central Java Regional Police are as follows: Community legal awareness is not optimal, there are limitations in facilities and infrastructure and very few cases have reached trial. Efforts made to overcome obstacles in law enforcement against online prostitution in the jurisdiction of the Central Java Regional Police include building partnerships with the wider community, improving facilities and facilities and for members should be given special training related to investigations into acts, online prostitution crime